2016
DOI: 10.1016/j.cplett.2015.08.038
|View full text |Cite|
|
Sign up to set email alerts
|

Polyethylene glycol gold-nanoparticles: Facile nanostructuration of doxorubicin and its complex with DNA molecules for SERS detection

Abstract: We report the synthesis of dicarboxylic acid-terminated polyethylene-glycol (PEG)-gold nanoparticles by a simple one-step method, and their further use to form nanostructured surfaces for biomolecule immobilization. The synthesized nano-scale particles were conjugated with probe/target oligonucleotides in order to evaluate intercalation phenomenon in the presence of doxorubicin drug via Surface Enhanced Raman Spectroscopy (SERS) analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…SERS studies of DNA damage primarily focus on the interaction of chemotherapeutic drugs with the DNA molecule. The impact of doxorubicin on oligonucleotide structure was studied by Spadavecchia et al, using pegylated gold nanoparticles (PEG-AuNPs) covalently linked to the cysteamine-gold surface via amide bond, as a SERS substrate [100]. SERS band at 1591 cm −1 confirms the formation of the DNA-doxorubicin complex.…”
Section: Sersmentioning
confidence: 99%
See 1 more Smart Citation
“…SERS studies of DNA damage primarily focus on the interaction of chemotherapeutic drugs with the DNA molecule. The impact of doxorubicin on oligonucleotide structure was studied by Spadavecchia et al, using pegylated gold nanoparticles (PEG-AuNPs) covalently linked to the cysteamine-gold surface via amide bond, as a SERS substrate [100]. SERS band at 1591 cm −1 confirms the formation of the DNA-doxorubicin complex.…”
Section: Sersmentioning
confidence: 99%
“…The SERS bands characteristic for doxorubicin-DNA interaction are presented in Table 2. The doxorubicin interaction with dsDNA was studied in various SERS configurations, using different SERS enhancers [100,[107][108][109], which resulted in a shift in the spectral position of characteristic bands, or a change in their intensity. In many cases, the bands corresponding to the in-plane bending of hydroxyl groups at doxorubicin rings, usually found around 1210 and 1244 cm −1 , were very weak or absent in the SERS spectrum, owing to drug intercalation into dsDNA structure [101,107].…”
Section: Sersmentioning
confidence: 99%
“…In particular, S.Yang et al have indicated that citric acid makes complexes with Au­(III) at several pH values, affecting the particle size . In this case, PEG diacide, about citric acid, intervenes the formation of complex PEG–Au­(III)–Drug for the growth of NPs. ,, …”
Section: Resultsmentioning
confidence: 99%
“…The decrease in intensity of the bands at 1214 and 1246 cm −1 assigned to in-plane C-O, C-O-H vibrations and C-H bending confirms the intercalation of doxorubicin rings within the DNA structure. The studies on DNA-doxorubicin binding process using synthesized nanoscale particles with probe/target oligonucleotides as a SERS substrate were continued by Spadavecchia et al [93]. Presence of the doxorubicin-DNA complex was confirmed by appearance of the band at 1591 cm −1 in the SERS spectrum.…”
Section: Protective Role Of Solventsmentioning
confidence: 98%